Law for Ensuring Data Security in the Digital Age: Challenges for Government and Warnings for Us - Duha, Ariskita (CV WAHANA PUBLIKASI, 2024)
The rapid development of information technology in the digital era poses serious challenges to personal data protection. Data leakage, misuse of information, and unauthorized surveillance are real threats that require a comprehensive legal response. This study aims to analyze the extent of the role of law in ensuring data security in Indonesia, as well as evaluate the effectiveness of Law Number 27 of 2022 concerning Personal Data Protection. This study uses a normative juridical approach with a literature study method and comparative analysis of the General Data Protection Regulation (GDPR) as a reference for international standards. The results of the study show that even though Indonesia already has a formal legal basis through the PDP Law, the implementation of data protection still faces various obstacles. Among them are the lack of independent, authoritative institutions, the lack of public literacy related to digital privacy, and weak law enforcement against data breaches. A comparative study with GDPR confirms that Indonesia’s legal framework is not yet equal in terms of transparency, accountability, and oversight of data controllers. The conclusion of this study shows that structural and substantial efforts are needed to strengthen the data protection legal system, including the drafting of technical regulations, institutional strengthening, and increasing the capacity of law enforcement human resources. The implications of this study emphasize the importance of regulatory reform and a multidisciplinary approach between law and technology to create an effective and equitable data protection system.